EXTH-87. DECITABINE POTENTIATES MENINGIOMA IMMUNOTHERAPY TARGETING NY-ESO-1. (14th November 2022) - Sun, Matthew; Orpilla, Joey; Contreras, Erick; Imbroane, Marisa; Treger, Janet; Wang, Anthony; Ko, MyungJun; Vitte, Jeremie; Giovannini, Marco; Liau, Linda M; Prins, Robert; Everson, Richard G
Abstract: INTRODUCTION: No immunotherapy exists for meningiomas. NY-ESO-1 is a potential target because in meningiomas it's the most frequently expressed Cancer-Testis-antigen. Decitabine is a hypomethylating agent known to upregulate CT-antigens. We tested the effects of decitabine on NY-ESO-1 expression in primary and immortalized meningioma cultures, and its impact on the efficacy of NY-ESO-1 T-cell-receptor-transduced T-cells(TCRs), to understand its potential role in meningiomas immunotherapy. METHODS: We established primary meningiomas cultures from fresh tumor specimens and quantified NY-ESO-1 expression using Western blot and qRT-PCR. Cultures were pre-treated with 1uM of decitabine for at least 48 hours before assays. In vitro cytolysis was measured using the xCelligence Real-Time Cell Analyzer System in meningioma co-cultures with MHC-Class-I(HLA-A*0201)–restricted NY-ESO-1(157 – 165) -specific TCRs. RESULTS: Nine primary and three immortalized meningioma cultures(Grade I – III) were evaluated for baseline NY-ESO-1 expression. High expression was defined as > 100-fold overexpression compared to glioma(U251) cultures. Decitabine treatment significantly increased NY-ESO-1 expression in 6 primary and 2 immortalized(SF1335, grade 1; IOMM-LEE, grade 3) cultures with low baseline expression(median increase over 100 fold; p > 0.001); whereas it slightly decreased NY-ESO-1 expression in 3 primary and 1 immortalized culture(CH157, WHO grade 3) with high baseline expression(median decrease 20%;p< 0.001). Decitabine pre-treatment of meningioma before co-culture with NY-ESO-1 TCRs at a ratio of 1:1, increased tumor cytolysis for SF1335, from 20% to 40%, and for IOMM-LEE, from 0% to 85%, measured at 10 hours. NY-ESO-1 expression increased 5000-fold vs 10-fold for IOMM-LEE vs SF1335, respectively. Decitabine treatment also increased MHC-Class-I expression for IOMM-LEE but not SF1335. Decitabine pre-treatment did not change cytolysis of CH157 at 65%(10 hrs). CONCLUSIONS: Decitabine upregulates NY-ESO-1 expression in meningiomas with low baseline expression, and it increases cytolytic effects of NY-ESO-1 TCRs proportional to NY-ESO-1 and MHC-Class-I molecule upregulation. Decitabine may be a clinically feasible adjunct to meningioma immunotherapy.